Working with all nations and all relatives in feeding the future - Shaileshkumar Shukla (Canadian Food Studies)
Most unprecedented changes and challenges to planetary health that include earth and human health, are attributed to short-sighted policies and systemic barriers. Standardized and top-down approaches of development that often dominate through limited, persuasive, and extractive euro-centric perspectives often dominate in Turtle Island and most colonial regions of the world. Food and food-sustaining relatives (land, water, plants, animals, micro-habitats) which are central to planetary health, are negatively impacted and threatened by these human pressures, which have severe implications for our ability to feed current and future generations (FAO et al., 2023; Planetary Health Alliance, n.d.). Many international agencies (including those affiliated with the United Nations), food systems scholars, grassroots organizations, and community members are grappling with the very imminent challenges of addressing the alarmingly high level of food insecurity in Turtle Island (Council of Canadian Academics, 2014; Fieldhouse & Thompson, 2012) and the global South (Kuhnlein et al., 2013).